2009
DOI: 10.1021/ac9021117
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Prothrombin Time in Human Whole-Blood Samples with a Quartz Crystal Biosensor

Abstract: Monitoring of blood coagulation and fibrinolysis is an important issue in treatment of patients with cardiovascular problems and in surgery when blood gets into contact with artificial surfaces. In this work a new method for measuring the coagulation time (prothrombin time, PT) of human whole-blood samples based on a quartz crystal microbalance (QCM) biosensor is presented. The 10 MHz sensors used in this work respond with a frequency shift to changes in viscosity during blood clot formation. For driving and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 28 publications
(32 reference statements)
4
45
0
Order By: Relevance
“…This phenomenon provides a sensitive and convenient method for measuring the Tc values of clots. 17,19 Figure 4 plots a typical response curve of the ∆F 2 measured by the QCM during clot formation, which is similar to curves presented elsewhere. 17,21 Briefly, recalcified blood samples containing the various NPs were loaded onto a QCM sensor, which rapidly reduced its frequency, by approximately 4KHz, within approximately 30 seconds.…”
Section: Blood Tc Was Reduced By Hemostatic Nps Evaluated By Measurinsupporting
confidence: 58%
See 2 more Smart Citations
“…This phenomenon provides a sensitive and convenient method for measuring the Tc values of clots. 17,19 Figure 4 plots a typical response curve of the ∆F 2 measured by the QCM during clot formation, which is similar to curves presented elsewhere. 17,21 Briefly, recalcified blood samples containing the various NPs were loaded onto a QCM sensor, which rapidly reduced its frequency, by approximately 4KHz, within approximately 30 seconds.…”
Section: Blood Tc Was Reduced By Hemostatic Nps Evaluated By Measurinsupporting
confidence: 58%
“…28 Interestingly, the ∆F 2 values obtained in this study were similar to those revealed by the oscillatory circuit in the QCM with dissipation monitoring (QCM-D) technique, which is used to detect mass deposition or changes in the viscosity of adjacent liquids or blood clots on quartz sensors. 17,19 Although the energy dissipation attributable to the differences in viscosity and density among the clot/PBS and others could not be evaluated by this QCM system, the SEM morphologies of the clots analyzed herein indicated the variation in ∆F 2 values among clots. The SEM morphologies in Figure 3 Figure 4D), according to the equation of Kanazawa and Gordon.…”
Section: Blood Tc Was Reduced By Hemostatic Nps Evaluated By Measurinmentioning
confidence: 83%
See 1 more Smart Citation
“…Detailed information can be obtained from our previous studies on blood plasma viscosity 21,22 . During blood coagulation, a sudden change in the blood plasma viscosity occurs due to fibrin generation 13 . This kind of viscosity change creates an increase in the hydrodynamic loading of the vibrating structures in viscous liquids according to Sader's theory 27 .…”
Section: Characterization Of the Systemmentioning
confidence: 99%
“…The researchers utilized microfluidic platforms [3], Quartz Crystal Microbalance (QCM) [4,5] Film Bulk Acoustic Resonator (FBAR) [6] based techniques for clot-time measurements. But they are limited to single tests and not multiplexed.…”
Section: Introductionmentioning
confidence: 99%